Six-sigma Methodologies in Airlines Operations - Ramesh Bollapragada; Vivian Chan
In this paper, we illustrate the key improvement indicators, their performance variance, and their respective financial impacts on airline operations. Through the six sigma process improvement methodology (DMAIC), this paper presents the passengers$1 (Bexpectations, current performance level, compensation expenses due to nonconformities, root causes of the nonconformities, and means to reduce performance variance and improve process to achieve cost savings. The research methods consist of data collection from several sources such as SITA, U.S. Aviation consumer reports, Aviation accident statistics from multiple sources. Our results indicate airlines can save billions of dollars annually once six sigma operational processes are reached.s